Intertextuality in Pre-service Teachers’ Argumentative Essay in Raising AI: Practices and Beliefs - Martono; Nur Arifah Drajati; Dewi Rochsantiningsih; Surya Agung Wijaya (UIN Salatiga, 2023)
English as Foreign Language (EFL) pre-service teachers arguably face more challenges regarding rhetorical moves in argumentative essays, and one of them is intertextuality because EFL pre-service teachers' arguments require sufficient and high-quality support and evidence from other scholars. Intertextuality was mainly studied, grounding in texts without external tools, for instance, Artificial Intelligence (AI). In raising the AI era, the objective of this study is to investigate Indonesian EFL pre-service teachers' intertextuality in argumentative essays assisted by AI. Ten EFL pre-service teachers who attended sixteen courses in Academic Writing with neither teaching nor writing experience were recruited as participants. We employed a case study design to portray the nature of the phenomena, and the data were collected through documents (academic essays) to portray the practices, and interviews to represent teachers' beliefs on explicit and implicit intertextuality beyond their argumentative essays in facing AI. We employed content analysis from academic essays and interviews. The findings shows that that 1) EFL pre-service teachers mostly used reporting phrases and iconic references, but it was oriented to local references that targeted local audiences, so international references should be more practiced; and 2) EFL pre-service teachers' beliefs that assisted AI while writing argumentative essay was limited to writing accuracy, but it helped them to focus on intertextuality. Although they were enough to give sufficient intertextuality references in practice, they could not present their voices to tailor their arguments. Moreover, the intertextuality praxis and policy implications will be discussed in EFL pre-service teachers' argumentative essays assisted by AI.